(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The creative work of K.Vonnegut is studied due to the importance of his literary heritage not only in the American literature, but also the enormous influence of his works on the world art process of the 20th century. K.Vonnegut was a comedy dramatist, a master of satire, black humor and science fiction. Skillfully combining various postmodern techniques in his prose, the writer described the realities of society, the consequences of war and human destinies with great skill. On the first page of most of his works, Kurt Vonnegut used metafiction. Metafiction – is a summary of events that reflects on himself and implies a violation of the boundary between the inner world of the work and the world of literary creation. The writer had a unique manner of describing the little things of real life, thereby creating the fragmentation of his prose. At the same time, the author resorted to irony to describe the stupidity and insignificance of the real world. While describing events, K.Vonnegut often used black humor, which he called soft laughter, emphasizing the need for literature in this genre. For example, analyzing the work «Slaughterhouse No 5», the researchers agree that it was the use of black humor that put this work on a par with the works of prominent authors of the 20th century. Using black humor while describing death, the author creates in the reader a feeling of its absolute unimportance, causing nausea and emphasizing the absurdity of the world. At the end of the work, the reader hates war as does Kurt Vonnegut. Having perfectly studied the lower layer of the American life, the writer was able to fully reveal the causes of moral backwardness, internal contradictions of society with the help of convincing artistic colors, typification, symbolization. Along with black humor, Kurt Vonnegut used such literary tools as fiction, grotesque and sarcasm. And with a deeper analysis, we will see that the writer used a large number of epithets, comparisons and metaphors in his novels and articles. In addition, Vonnegut’s prose is autobiographical. Regardless of what event the writer spoke about, he almost always resorted to personal experience, thereby making the work even more interesting giving funny or, on the contrary, tragic examples. In this sense, the reason that some of Vonnegut’s novels have a preface and others lack it is simple. The author used the autobiographical preface if the problems discussed in the book concerned the writer directly and were more of a private nature. And in the case of global problems, there was no need to update them through personal examples, since they were already clear to the vast majority of readers.